Ongoing Risk of Ventricular Arrhythmias and All-Cause Mortality at Implantable Cardioverter Defibrillator Generator Change: A Systematic Review and Meta-Analysis. (6th February 2021) - Yuyun, Matthew F.; Erqou, Sebhat A.; Peralta, Adelqui O.; Hoffmeister, Peter S.; Yarmohammadi, Hirad; Echouffo-Tcheugui, Justin B.; Martin, David T.; Joseph, Jacob; Singh, Jagmeet P.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Uncertainty still surrounds implantable cardioverter defibrillator (ICD) generator change at time of elective replacement indicator, in primary prevention patients with improved left ventricular ejection fraction (LVEF) beyond guideline recommendations or without prior appropriate ICD therapies. Methods: We conducted a meta-analysis of studies assessing the risk of appropriate ICD therapies and all-cause mortality after generator change in patients with improved LVEF>35% versus unimproved LVEF≤35% or patients without versus with prior appropriate ICD therapies during the life of their first ICD generator. A systematic electronic search of PubMed, EMBASE, and Cochrane Library databases until December 31, 2019 was performed. Estimates were combined using random-effects model meta-analyses. Results: In 15 studies that included 29 730 patients, 25.3% had LVEF improvement >35% at time of generator change. The pooled annual incidence of appropriate ICD therapies was significantly lower in those with improved LVEF, compared with patients with unimproved LVEF: 4.6% versus 10.7%; risk ratio, 0.50 (95% CI, 0.36–0.68), P <0.0001. The pooled rate of all-cause mortality was 6.6% versus 10.9% per year, risk ratio of 0.65 (95% CI, 0.62–0.69), P <0.0001. Risk of inappropriate shock was comparable between the 2 groups ( P =0.750). In 8 studies (N=27 209), the pooled incidence of ventricular arrhythmia was significantly lower in patients without prior ICD therapies (3.9% per annum), compared with those with prior ICD therapies (12.5 % per annum), risk ratio of 0.37 (95% CI, 0.33–0.41), P <0.001. Conclusions: There was significant reduction in risk of ventricular arrhythmias and mortality in patients with improved versus unimproved LVEF or those who received versus those who did not receive appropriate ICD therapies during the life of their first ICD generator. However, we found a substantial residual outcome risk in these groups of patients.